DEVELOPMENT AND VALIDATION OF OSIMERTINIB IN TABLET DOSAGE FORM BY RP-HPLC - ICH Guidelines; K, Usha; l, Harikiran (International Journal of Pharmacy and Analytical Research, 2025)
A simple, rapid, specific and accurate reverse phase high performance liquid chromatographic method has been developed for the validated of Osimertinib in bulk as well as in marketed pharmaceutical dosage form. This separation was performed on a Symmetry ODS C18 (4.6×250mm, 5µm) column with Methanol: Phosphate Buffer (35:65) V/V as mobile phase at a flow rate of 1.0 mL min−1 with UV detection at 235 nm; the constant column temperature was Ambient. The run time under these chromatographic conditions was less than 8 min. The retention time of Osimertinib was found to be 2.252. The calibration plot was linear over the concentration range of 6–14μg mL−1 with limits of detection and quantification values of 1.2 and 3.6ng mL−1 respectively. The mean % assay of marketed formulation was found to be 99.86%, and % recovery was observed in the range of 98-102%. Relative standard deviation for the precision study was found <2%.The developed method is simple, precise, specific, accurate and rapid, making it suitable for estimation of Osimertinib in bulk and marketed pharmaceutical dosage form dosage form.